Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Kabupaten Purwakarta - Mirnawati; Dadan Ahmad Fadili; Arif Fadilla (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of competence and work discipline on employee performance at the Purwakarta Regency Environmental Agency, both partially and simultaneously. A quantitative approach utilizing descriptive and verificative methods was employed. The study population consisted of 111 Civil Servants (PNS), all of whom were included in the sample using a saturated sampling technique. Data collection was conducted through questionnaires, interviews, and literature reviews, while data analysis involved multiple linear regression, the coefficient of determination, t-tests, and F-tests using SPSS version 26. The results indicate that competence has a positive and significant partial effect on employee performance, with a calculated t-value of 2.817 and a significance level of 0.006 (< 0.05). Work discipline also has a positive and significant partial effect on employee performance, with a calculated t-value of 5.241 and a significance level of 0.000 (< 0.05). Simultaneously, competence and work discipline exert a positive and significant influence on employee performance, with a calculated F-value of 73.854 and a significance level of 0.000 (< 0.05). The Adjusted R-Square value of 0.570 indicates that competence and work discipline account for 57% of the variation in employee performance. The study concludes that competence and work discipline—both partially and simultaneously—have a positive and significant impact on employee performance, with work discipline exerting a more dominant influence than competence. Keywords: Work Discipline, Employee Performance, Competence, Civil Servant, Human Resources